Robert Lansing papers - Lansing, Robert, 1864-1928.
Correspondence, memoranda, reports, resolutions, desk diaries, book manuscripts, speeches, scrapbooks, clippings, printed material, memorabilia, photographs, and other papers relating chiefly to Lansing's years (1914-1920) as counsel to the Dept. of State and as secretary of state and particularly to American foreign relations during World War I, the Paris Peace Conference, and Lansing's relations with President Woodrow Wilson and with various foreign diplomats and statesmen. Includes material on the Lusitania affair, the Mexican crisis, the arming of merchant seamen, the Irish rebellion, the purchase of the Danish West Indies, relations with Japan and China, and Latin America and the proposed Pan American Pact. Personal papers concern Lansing's participation in private legal cases involving international law and his activity in domestic politics. Includes the draft of Lansing's war memoirs, published in part in 1935.
Correspondents include Chandler P. Anderson, Frederick M. Boyer, William Jennings Bryan, Viscount James Bryce, John W. Davis, J. M. Dickinson, Allen Welsh Dulles, John Foster Dulles, Abram I. Elkus, John Watson Foster, Paul Fuller, James Watson Gerard, John Grier Hibben, Cone Johnson, J. J. Jusserand, V. K. Wellington Koo, Franklin K. Lane, Henry Cabot Lodge, Wayne MacVeagh, Thomas R. Marshall, Alexander Meiklejohn, John Bassett Moore, Henry Morgenthau, William Phillips, Frank L. Polk, Elihu Root, L. S. Rowe, James Brown Scott, Edward North Smith, William Joel Stone, Seymour Van Santvoord, Brand Whitlock, Woodrow Wilson, and Lester Hood Woolsey.
In part, available on microfilm
Microfilm produced from originals in the Manuscript Division.
Lawyer, diplomat, secretary of state during the administration of President Woodrow Wilson, and member of the American mission to negotiate a peace treaty following World War I.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Anderson, Chandler P. -- 1866-1936 -- Correspondence; Boyer, Frederick M. -- Correspondence; Bryan, William Jennings, -- 1860-1925 -- Correspondence; Bryce, James Bryce, -- Viscount, -- 1838-1922 -- Correspondence; Davis, John W. -- 1873-1955 -- Correspondence; Dickinson, J. M. -- 1851-1928 -- Correspondence; Dulles, Allen, -- 1893-1969 -- Correspondence; Dulles, John Foster, -- 1888-1959 -- Correspondence; Elkus, Abram I., -- 1867-1947 -- Correspondence; Foster, John Watson, -- 1836-1917 -- Correspondence; Fuller, Paul, -- -1947 -- Correspondence; Gerard, James Watson, -- 1867- -- Correspondence; Hibben, John Grier, -- 1861-1933 -- Correspondence; Johnson, Cone, -- 1860-1933 -- Correspondence; Jusserand, J. J. -- 1855-1932 -- Correspondence; Koo, V. K. Wellington, -- 1888-1985 -- Correspondence; Lane, Franklin K. -- Correspondence; Lodge, Henry Cabot, -- 1850-1924 -- Correspondence; MacVeagh, Wayne, -- 1833-1917 -- Correspondence; Marshall, Thomas R. -- 1854-1925 -- Correspondence; Meiklejohn, Alexander, -- 1872-1964 -- Correspondence; Moore, John Bassett, -- 1860-1947 -- Correspondence; Morgenthau, Henry, -- 1856-1946 -- Correspondence; Phillips, William, -- 1878-1968 -- Correspondence; Polk, Frank L. -- 1871-1943 -- Correspondence; Root, Elihu, -- 1845-1937 -- Correspondence; Rowe, L. S. -- 1871-1946 -- Correspondence; Scott, James Brown, -- 1866-1943 -- Correspondence; Smith, Edward North, -- 1868-1943 -- Correspondence; Stone, William Joel, -- 1848-1918 -- Correspondence; Van Santvoord, Seymour, -- 1858-1938 -- Correspondence; Whitlock, Brand, -- 1869-1934 -- Correspondence; Wilson, Woodrow, -- 1856-1924 -- Correspondence; Woolsey, Lester Hood, -- 1877-1961 -- Correspondence; Lusitania (Steamship); Diplomatic and consular service, American; International law; Merchant marine -- United States -- History -- 20th century; World War, 1914-1918 -- Diplomatic history; World War, 1914-1918 -- Personal narratives; World War, 1914-1918 -- Transportation; China -- Foreign relations -- United States; Ireland -- History -- Sinn Fein Rebellion, 1916.; Japan -- Foreign relations -- United States; Latin America -- Foreign relations -- United States; Mexico -- Foreign relations -- United States; United States -- Foreign relations -- China; United States -- Foreign relations -- Japan; United States -- Foreign relations -- Latin America; United States -- Foreign relations -- Mexico; United States -- Politics and government -- 1913-1921.; Virgin Islands; Cabinet officers; Statesmen